Morphological changes in the human mandible associated with the presence of exostoses: A cross-sectional study in two archaeological populations from southern France - Estelle Casazza; Benoit Ballester; Camille Philip-Alliez; Yann Ardagna; Anne Raskin (PLoS ONE, 2025)
This cross-sectional study aimed to investigate morphological changes in the human mandible in archaeological collections associated with the presence of bony exostoses at the mandibular angle, which is described in the literature as related to specific behaviours of the masticatory apparatus like parafunctional activities. The skeletal sample investigated comprised adult individuals from two archaeological series. Sixteen measurements of the mandible were selected to evaluate anatomic variation in the two populations. Mandibles from both series were pooled for statistical analysis into two groups according to the number of exostoses at the mandibular angles: group 1 (number of exostoses ≤1) and group 2 (number of exostoses ≥ 2). Measurements could be made on eighty mandibles. A statistically significant difference was demonstrated between group 1 and group 2 for the following parameters: distance between mandibular angles, bicondylar width, ramus height, left condyle length, and right and left coronoid process height. For each of these parameters, values were higher in group 2 than in group 1. This study presents an original methodology for studying anatomical variations of the mandible in the context of parafunctional activity, highlighting certain mandibular modifications. The impact of parafunctional behaviours such as bruxism on the mandible therefore has many anatomical expressions. The considerable variability of results found in the literature shows that more studies are needed to reach a consensus on the impact of parafunctional activities on the mandible.